Peran Guru IPS Dalam Membentuk Karakter Siswa Kelas VII di SMP Negeri 3 Maumere - Ayuni Ayuni; Rimasi Rimasi (Universitas Maritim AMNI Semarang, 2023)
This research seek to show how social studies teachers at SMP Negeri 3 Maumere help class VII students develop an honest, disciplined, pious, and responsible character. This study employs a qualitative methodology and uses methods including observation, interviews, and documentation to gather data. According to the study's findings, teachers play a significant impact in influencing class VII students' character development, particularly when it comes to social studies instruction. Because teachers not only instruct students in moral principles on a theoretical level, but also set an example for them, their job in forming students' character has been optimally carried out.